Development of a rehabilitation programme for young adult cancer survivors using co-production - Maria Aagesen; Marc Sampedro Pilegaard; Astrid Janssens; May Aasebø Hauken; Karen la Cour (Research Involvement and Engagement)
Abstract Background Young adult cancer survivors, defined as individuals aged 18–39 who have completed primary curative treatment, face numerous age-specific biopsychosocial late effects that impact health-related quality of life negatively. Rehabilitation can enhance participation in life roles, work, leisure activities and health-related quality of life. However, there is a lack of age-specific cancer rehabilitation for this population, leaving many young adults with diminished self-efficacy in managing their challenges, resulting in unmet needs. This study aimed to co-produce and develop an age-specific, municipality-based cancer rehabilitation intervention programme to improve young adults’ self-efficacy and health-related quality of life. Methods The development process was completed between September 2019 and June 2023 and followed Hawkins et al.’s three-staged framework for co-production: (1) A literature review and stakeholder consultations; (2) four workshops with 2–6 young adult cancer survivors, 3–4 professionals, and two researchers and one workshop with 20 young adult cancer survivors and two researchers to co-produce the name, component content, delivery methods and potential outcomes; and (3) Refinement of the programme and its programme theory. Key findings from each stage informed the subsequent stages. Results The Young Adults Taking ACtion programme was developed. It applies a person-centred approach and is grounded in social cognitive theory and experiential learning theory. It comprises one mandatory component, a needs assessment and goal setting that tailor which of the following seven components the young adults will receive: (1) everyday life, (2) physical activity, (3) psychological issues, (4) education and work, (5) sexuality and relationships, (6) funds and grants, and (7) family and friends. The programme is primarily group-based and will be delivered by an interdisciplinary team over 16 weeks. Conclusions We co-produced a comprehensive, goal-oriented, and peer-based rehabilitation programme for young adult cancer survivors. The engagement of young adults and professionals ensured that the programme aligned with the population’s needs and preferences and was context specific. Thus, it is likely that the programme will be more realistic and feasible to implement in clinical practice.